IMPLEMENTASI NILAI GOTONG ROYONG DAN KEPEDULIAN SOSIAL DALAM TRADISI LIBOTAN DI DESA PEMARON KABUPATEN BREBES DALAM PERSPEKTIF SOSIAL BUDAYA - Sugeng Riyadi; Tity Kusrina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article aims to examine the implementation of communal cooperation (gotong royong) and social care values in the Libotan tradition of Pemaron Village, Brebes Regency, Central Java. Using a literature review method, this study synthesizes previous research findings concerning communal cooperation, social care, and local traditions in Indonesian rural societies. The review reveals that local traditions like Libotan function as social frameworks where the values of cooperation and social solidarity are manifested through collective labor, mutual assistance, and community participation. However, modernization and socio‐economic transformation pose challenges to the sustainability of these values. The article proposes a conceptual framework and field research instruments to empirically analyze these dynamics in Pemaron. The findings contribute to the academic discourse on sustaining local wisdom and social cohesion in Indonesian rural communities.